Strategi Roleplaying dalam Pembelajaran PPKN untuk Menumbuhkan Sikap Demokratis Siswa Sekolah Dasar - Zakia, Aziza Rahma; Noviana, Lena; Septiana, Ria; Salfadilah, Fatonah (Insight: Indonesian Journal of Social, Humanity, and Education, 2025)
Civic Education (PPKn) has a vital role in developing students’ democratic character and civic awareness, especially in the era of the Merdeka Curriculum (2020–2025), which emphasizes active, value-based learning. However, recent findings indicate that most elementary schools in Indonesia still rely on teacher-centered lectures, resulting in low student participation and limited internalization of democratic values. This study aims to analyze the implementation of the role playing strategy as an active learning approach to foster democratic attitudes among elementary school students. Using a systematic literature review method, fifteen scholarly articles published between 2020 and 2025 were examined to identify the effectiveness of role playing in PPKn learning. The analysis shows that role playing significantly enhances students’ participation, communication, empathy, cooperation, and social responsibility. It also provides authentic experiences in deliberation, problem-solving, and joint decision-making that reinforce democratic behavior in daily life. Theoretically, this strategy aligns with Kolb’s Experiential Learning Theory and Vygotsky’s Social Constructivism, emphasizing that knowledge and values are best acquired through meaningful social experiences. The study concludes that role playing is an effective and contextually relevant approach to strengthening democratic education in elementary schools. Future research is recommended to conduct classroom-based experiments to provide empirical evidence and further develop innovative civic learning models that nurture democratic citizens in the digital era. [Pendidikan Pancasila dan Kewarganegaraan (PPKn) memiliki peran penting dalam membentuk karakter dan sikap demokratis siswa, khususnya pada era Kurikulum Merdeka tahun 2020–2025 yang menekankan pembelajaran aktif dan berpusat pada nilai. Namun, berbagai penelitian menunjukkan bahwa pembelajaran PPKn di sekolah dasar masih didominasi oleh metode ceramah yang bersifat teacher-centered, sehingga siswa kurang berpartisipasi aktif dan belum mampu menginternalisasi nilai-nilai demokrasi secara optimal. Penelitian ini bertujuan untuk menganalisis penerapan strategi role playing sebagai pendekatan pembelajaran aktif dalam menumbuhkan sikap demokratis siswa sekolah dasar. Metode yang digunakan adalah studi literatur sistematis terhadap lima belas artikel ilmiah terbitan tahun 2020–2025 yang membahas efektivitas role playing dalam pembelajaran PPKn. Hasil analisis menunjukkan bahwa strategi ini mampu meningkatkan partisipasi siswa, keterampilan komunikasi, empati, kerja sama, dan tanggung jawab sosial. Selain itu, role playing memberikan pengalaman belajar langsung yang melatih kemampuan musyawarah, pemecahan masalah, dan pengambilan keputusan bersama yang mencerminkan perilaku demokratis dalam kehidupan nyata. Secara teoretis, strategi ini sejalan dengan teori Experiential Learning (Kolb) dan Konstruktivisme Sosial (Vygotsky), yang menekankan pentingnya pengalaman sosial bermakna dalam pembentukan nilai dan karakter. Dengan demikian, role playing merupakan strategi yang efektif dan relevan diterapkan dalam pembelajaran PPKn di sekolah dasar. Penelitian selanjutnya disarankan melakukan eksperimen lapangan untuk menguji efektivitas empiris dan mengembangkan inovasi pembelajaran kewarganegaraan berbasis nilai demokratis.]